Sustainability reporting quality: The effect of good corporate governance, gender diversity, and company age - Amatullah, Azhura Nawwaf; Suharman, Harry; Fatmawati, Faoziah Ulfah (Journal of Accounting Auditing and Business, 2025)
This study aims to determine the effect of good corporate governance (GCG), gender diversity, and company age on sustainability reporting quality. The three independent variables used include good corporate governance, gender diversity, and company age, with sustainability reporting quality as the dependent variable. This study used a sample of 44 companies from the manufacturing, energy, and financial sectors listed on the Indonesia Stock Exchange (IDX) in 2023. This research uses quantitative methods with secondary data obtained from various sources, such as Refinitiv Datastream and ESGI Dataset, as well as sustainability reports and annual reports in 2023. Data were collected through literature studies and documentation. The results showed that good corporate governance significantly positively affects sustainability reporting quality. However, gender diversity and company age do not significantly affect sustainability reporting quality. GCG implementation is essential in improving sustainability reporting quality through transparency and accountability, resulting in a more comprehensive and quality sustainability report.